2010
DOI: 10.2310/7750.2010.09066
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Moderate-to-Severe Plaque Psoriasis in a Canadian Surveyed Population

Abstract: the findings are consistent with a substantial burden attributed to moderate-to-severe plaque psoriasis in a Canadian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Twenty‐two studies provided data on the natural history and long‐term outcomes of child‐onset psoriasis . Ten studies reported the percentage of adult patients with psoriasis with child‐onset disease.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies provided data on the natural history and long‐term outcomes of child‐onset psoriasis . Ten studies reported the percentage of adult patients with psoriasis with child‐onset disease.…”
Section: Resultsmentioning
confidence: 99%
“…Limitations to this study, as detailed elsewhere, 28,41 include the use of pre‐existing Canadian consumer panels and databases. Although these databases are developed with the intention that they should be representative of the general population, it should be noted that study subjects were not randomly sampled and may not necessarily be truly representative of the Canadian population.…”
Section: Discussionmentioning
confidence: 99%
“…Effective patient education is critical, 39 as is strengthening communication between patients and physicians, which should include a joint decision-making process and the selection of appropriate treatment options to improve overall management. 23,32,39,40 Limitations to this study, as detailed elsewhere, 28,41 include the use of pre-existing Canadian consumer panels and databases. Although these databases are developed with the intention that they should be representative of the general population, it should be noted that study subjects were not randomly sampled and may not necessarily be truly representative of the Canadian population.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a common immune-mediated inflammatory skin disease affecting 1–3% of the Canadian population [ 1 , 2 ]. It is characterized by sharply demarcated, erythematous, indurated plaques covered by silvery-white scales, as well as systemic comorbidities [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%